Factores de riesgo de lumbalgia y discapacidad laboral en los pacientes atendidos en el área de fisiatría del Hospital Regional Isidro Ayora - Novillo Valdivieso, María Soledad (2015)
Low back pain is a syndrome characterized by pain in the lumbosacral region, between the lower ribs and the buttocks. It affects 70% of the population in developed countries, having great impact on public health, the absenteeism it generates. Given its importance was raised to identify the risk factors involved in the onset of back pain and determine the degree of disability, and their influence on the employment situation of patients during the period February to July 2014; descriptive study was conducted cross-section, with a sample of 67 patients with low back pain in the area of physiatry the Isidro Ayora Hospital; a survey to determine risk factors and the Oswestry test for the degree of disability: data collection for 2 instruments used. As a result it was found that this disease is predominant in males (64%), affects patients aged 50-59 years (37%); and mostly it is nonspecific origin (51%); within occupational risk factors as major triggers more frequent back pain in tasks such as farmers (18%), construction workers (15%), nurses (13%), factors such as stress positions no ergonomics> 2h (28%) was determined , seated> 4h (19%), heavy lifting> to 6kg (15%); accounting for 41% of moderate functional limitations and 22% disability, causing 48% of sick leave. In conclusion the results of this study reveal an association between exposure to biomechanical risk factors and the presence of musculoskeletal injuries, indicating that forced work postures signify greater risk. Therefore, this type of lesion could incapacitate the patient in activities of daily living. Keywords: Low back pain, risk factors, work disability, patients.